Seeing how it works: A visual essay about critical and transformative research in education - Naydene de Lange; Relebohile Moletsane; Claudia Mitchell (Perspectives in Education, 2015)
As visual researchers in the field of education we have initiated and completed numerous participatory projects using qualitative visual methods such as drawing, collage, photovoice, and participatory video, along with organising screenings and creating exhibitions, action briefs, and policy posters. Locating this work within a critical paradigm, we have used these methods with participants to explore issues relating to HIV and AIDS and to gender-based violence in rural contexts. With technology, social media, and digital communication network connections becoming more accessible, the possibilities of using visual participatory methods in educational research have been extended. However, the value of visual participatory research in contributing to social change is often unrecognised. While the power of numbers and words in persuasive and informative change is well accepted within the community of educational researchers, the power of the visual itself is often overlooked. In this visual essay, we use the visual as a way to shift thinking about what it means to do educational research that is transformative in and of itself. As an example we draw on our visual participatory work with 15 first-year women university students in the Girls Leading Change1 project to explore and address sexual violence at a South African university. We aim to illustrate, literally, the possibilities of using the visual, not only as a mode of inquiry, but also of representation and communication in education and social science scholarship.